DEVELOPING THE CREATIVITY OF YOUNGER STUDENTS IN THE CONTEXT OF INNOVATIVE LEARNING - Зайырбек, Бақыткүл; Туралбаева , Алмаш (Журнал Педагогики и психологии в современном образовании, 2024)
The relevance of studying the psychological and pedagogical conditions conducive to fostering creativity in schoolchildren is determined by contemporary changes occurring in Russia, both in socio-economic and ideological spheres. These changes pose the task of shaping creative personalities to the educational system and require a reconsideration of existing teaching and upbringing methods. In response to these challenges, new types of educational institutions emerge, such as gymnasiums, lyceums, and colleges, oriented towards innovative approaches in education. Consequently, the development of students’ creativity becomes an important component of innovative learning, which adapts to its specificity.